Comparison of inhibitory effect between DL–tryptophan and lactoferrin on Pseudomonas aeruginosa biofilm formation in wound dressing - Eman Hussein Hussein Elfeky; Maii Atef Shams Eldeen; Amel Abd El-Tawab Hashish; Azza Mahmoud Hassan (Journal of Acute Disease, 2019)
Objective: To compare the inhibitory effect between DL-tryptophan and bovine lactoferrin on biofilm formed by isolated Pseudomonas aeruginosa strains. Methods: The study was carried out on 40 patients suffering from surgical site infection. Wound pus was collected using sterile swabs after isolation, and identified by common bacteriological methods. Isolated Pseudomonas aeruginosa strains were grown on biofilm enhancing materials, and then the inhibitory effects of different concentrations of DL-tryptophan and lactoferrin were tested using scanning electron microscopy and microtitre plate methods. Results: There was no significant difference in the inhibitory effect between DL-tryptophan and lactoferrin at 0.5 mg/mL. While in concentration of 1 mg/mL and 2 mg/mL, tryptophan showed more significant inhibitory effect than lactoferrin. Conclusions: Both DL-tryptophan and bovine lactoferrin have inhibitory effect on Pseudomonas aeruginosa biofilm formation in a dose dependent manner, and the inhibitory effect of DL- tryptophan is stronger.